Laser-Assisted Nanotexturing for Flexible Ultrathin Crystalline Si Solar Cells - Lee, Youngseok; Woo, Jeong-Hyun; Kim, Keonhee; Lee, Kyeong Seok; Jeong, Yeonjoo; Kim, Jaewook; Hwang, Gyu Weon; Lee, Doh-Kwon; Kim, Ju-Young; Kim, Inho (WILEY-V C H VERLAG GMBH, 2023)
Ultrathin (UT) crystalline Si wafers, which are more flexible than conventional ones, can apply to curved surfaces, enabling a wide range of applications such as building-integrated photovoltaics, vehicle-integrated photovoltaics, and wearable devices. Thinner wafers require more effective light trapping; thus, surface texturing in microscale is a common approach to compensate for the reduced thickness by enhancing the light pathlength. Microscale textures, however, deteriorate the mechanical flexibility due to stress concentration in the valley of the microtextures. In this study, a laser-assisted nanotexturing process is proposed for enhanced flexibility of the UT Si solar cells with a 50 & mu;m thickness while maintaining light-trapping performances. A nanolens array is used to focus laser onto the Si wafers, inducing the formation of nanoparticle etch masks for nanopyramid texturing in an alkaline solution. The origin of the enhanced flexibility of the nanotextured Si wafers is discussed by a micromechanics simulation study. Herein, nanotexturing technique is applied to UT Si-based passivated emitter rear cells and the enhanced flexibility of the cells with a 26 mm critical bending radius is demonstrated. Also, it is shown that the nanotextured Si wafer provides a higher efficiency of 18.68%, whereas the microtextured one exhibits 18.10%.